Intranasal inoculation of recombinant DNA vaccine ABA392 against haemorrhagic septicaemia disease - Kang, Tzin Lim; Chelliah, Shamini; Velappan, Rita Devi; Kabir, Nurul; Mohamad, Jamaludin; Rashid, Nurshamimi Nor; Ismail, Salmah (John Wiley & Sons, 2019)
We evaluate the efficacy of recombinant DNA vaccine ABA392 against haemorrhagic septicaemia infection through intranasal administration route by targeting the mucosal immunity. The DNA vaccine was constructed and subjected to animal study using the Sprague Dawley (SD) rat. The study was divided into two major parts: (i) active and (ii) passive immunization studies, involving 30 animals for each part. Each group was then divided into five test groups: two test samples G1 and G2 with 50 and 100 µg ml−1 purified DNA vaccine; one positive control G5 with 106 CFU per ml formalin-killed PMB2; and two negative controls, G3 and G4 with normal saline and pVAX1 vector. Both studies were conducted for the determination of immunogenicity by total white blood cell count (TWBC), indirect ELISA and histopathological changes for the presence of the bronchus-associated lymphoid tissue (BALT). Our findings demonstrate that TWBC, IgA and IgG increased after each of the three vaccination regimes: groups G1, G2 and G5. Test samples G1 and G2 showed significant differences (P < 0·05) compared to the negative controls, G3 and G4, but no significant differences from the positive control G5. Groups G1, G2 and G5 showed more formation of BALT compared to the negative controls, G3 and G4. Our results show that intranasal inoculation of recombinant DNA vaccine ABA392 can provoke mucosal immunity which makes it a potential prophylactic against HS. Significance and Impact of the Study: New approach of combating haemorrhagic septicaemia disease among bovines by recombinant DNA vaccine is crucial to overcome the loss of edible products from the infected bovines. DNA vaccine can potentially serve as a better immunogen which would elicit both cellular and humoral immunity, and it is also stable for its molecular reproduction. This research report demonstrates an effective yet simple way of administering the DNA vaccine via the intranasal route in rats, to provoke the mucosal immunity through the development of immunoglobulins IgA, IgG and bronchus-associated lymphoid tissue which guard as the first-line defence at the host's mucosal lining. © 2019 The Society for Applied Microbiology